From Mobile Screens to Awareness: Initiating Learning in Online Reproduction Classes as an Innovation in Health Promotion for Adolescents - M. Ridwan; Firda Fibrila; Herlina Herlina; Mariana Ngundju Awang; Andiyan Andiyan; Rofiqul Umam (Research and Community Service Unit, Poltekkes Kemenkes Kupang, 2026)
Adolescent reproductive health is a crucial issue directly related to the quality of life and future of the younger generation. Adolescent knowledge is a vital foundation for addressing reproductive health issues. Therefore, health promotion media that adapt to the needs and lifestyles of today's adolescents are necessary. This study aims to assess the effectiveness of digital reproduction classes as a learning medium for increasing adolescents' knowledge about reproductive health. It is hoped that this increased knowledge will stimulate awareness of the importance of reproductive health. This research is a single-group experimental study using a pre-post-test design for the trial of the reproductive health classes. The trial was conducted in three stages: a small-scale trial (n=7), a limited-scale trial (n=60), and a large-scale trial (n=380). Data were analyzed using a paired-sample t-test to compare knowledge scores before and after the intervention, and the N-Gain formula was used to assess class effectiveness. The small-scale trial increased the knowledge of 85.7% of participants, with an average increase of 14.3 points. The limited-scale trial showed an average increase of 15 points, while the large-scale trial showed an average increase of 15.54 points, with a p-value of 0.000 (95% CI: 16.67–14.42). The N-Gain score in the small-scale trial was 0.56, compared to 0.47 in the large-scale trial. The results demonstrate the effectiveness of the class in improving adolescents' knowledge. These findings reinforce the potential of online learning as an innovation in health promotion.